THU0363 EFFECTS OF NINTEDANIB IN PATIENTS WITH SYSTEMIC SCLEROSIS-ASSOCIATED ILD (SSC-ILD) AND NORMAL VERSUS ELEVATED C-REACTIVE PROTEIN (CRP) AT BASELINE: ANALYSES FROM THE SENSCIS TRIAL. (2nd June 2020) - Riemekasten, G.; Carreira, P.; Saketkoo, L. A.; Aringer, M.; Chung, L.; Pope, J.; Miede, C.; Stowasser, S.; Gahlemann, M.; Alves, M.; Khanna, D.
Abstract : Background: In the SENSCIS trial in patients with SSc-ILD, nintedanib reduced the rate of decline in forced vital capacity (FVC) over 52 weeks. Elevated CRP is a marker of an inflammatory phenotype and has been associated with a greater rate of decline in FVC and higher mortality in patients with SSc. Objectives: To assess the effects of nintedanib in subgroups by CRP at baseline in the SENSCIS trial. Methods: Patients with SSc-ILD with onset of first non-Raynaud symptom <7 years and ≥10% fibrosis of the lungs on HRCT were randomised to receive nintedanib or placebo. We analysed the rate of decline in FVC (mL/year) over 52 weeks, the proportion of patients with an absolute increase in FVC ≥3% predicted (proposed as the minimal clinically important difference for improvement in FVC in patients with SSc-ILD), and absolute change from baseline in mRSS at week 52 in subgroups with normal vs elevated high-sensitivity CRP (≤4.99 vs >4.99 mg/L) at baseline. Results: Of patients with available data, 78/270 (28.9%) and 74/261 (28.4%) in the nintedanib and placebo groups, respectively, had CRP >4.99 mg/L at baseline. Compared with patients with lower CRP, those with CRP >4.99 mg/L included a similar proportion of patients who were ATA-positive (61.8% vs 60.2%, respectively), a greater proportion with diffuse cutaneous SSc (63.2% vs 49.3%) and had a higher mean mRSS (13.7 vs 10.2) and lower mean FVC % predicted (68.6% vs 73.9%). The adjusted annual rate of decline in FVC in the placebo group was numerically greater in patients with CRP >4.99 than ≤4.99 mg/L at baseline (-106.6 [SE 27.6] vs -83.0 [17.1] mL/year). The effect of nintedanib vs placebo on reducing the rate of decline in FVC was numerically more pronounced in patients with CRP >4.99 than ≤4.99 mg/L at baseline but the treatment-by-time-by-subgroup interaction p-value did not indicate heterogeneity in the effect of nintedanib between subgroups (p=0.70) (Figure ). In the nintedanib and placebo groups, respectively, the proportions of patients with an absolute increase in FVC ≥3% predicted at week 52 were 20.4% and 15.0% in those with CRP ≤4.99 mg/L and 24.4% and 14.9% in those with CRP >4.99 mg/L at baseline (treatment-by-subgroup interaction p=0.59); adjusted mean changes in mRSS at week 52 were -2.2 (SE 0.3) and -2.1 (0.3) in those with CRP ≤4.99 mg/L (difference -0.1 [95% CI -1.0, 0.8]) and -2.3 (0.5) and -1.0 (0.5) in those with CRP >4.99 mg/L at baseline (difference -1.2 [-2.7, 0.2]; treatment-by-visit-by-subgroup interaction p=0.20). Conclusion: In the SENSCIS trial, the rate of decline in FVC over 52 weeks in the placebo group was numerically greater in patients with elevated CRP at baseline. Nintedanib reduced the rate of decline in FVC both in patients with normal and elevated CRP at baseline, with a numerically greater effect in patients with elevated CRP. Disclosure of Interests: Gabriela Riemekasten Consultant of: Cell Trend GmbH, Janssen, Actelion, Boehringer Ingelheim, Speakers bureau: Actelion, Novartis, Janssen, Roche, GlaxoSmithKline, Boehringer Ingelheim, Pfizer, Patricia Carreira Grant/research support from: Actelion, Roche, MSD, Consultant of: GlaxoSmithKline, VivaCell Biotechnology, Emerald Health Pharmaceuticals, Boehringer Ingelheim, Roche, Speakers bureau: Actelion, GlaxoSmithKline, Roche, Lesley Ann Saketkoo Grant/research support from: Corbus Pharmaceuticals, United Therapeutics, Consultant of: Boehringer Ingelheim, Eicos Sciences, Speakers bureau: Boehringer Ingelheim, Martin Aringer Consultant of: Boehringer Ingelheim, Roche, Speakers bureau: Boehringer Ingelheim, Roche, Lorinda Chung Grant/research support from: United Therapeutics, Boehringer Ingelheim, Consultant of: Bristol-Myers Squibb, Boehringer Ingelheim, Mitsubishi Tanabe, Eicos Sciences, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB, Corinna Miede Employee of: Employee of Boehringer Ingelheim, Susanne Stowasser Employee of: Employee of Boehringer Ingelheim, Martina Gahlemann Employee of: Employee of Boehringer Ingelheim, Margarida Alves Employee of: Employee of Boehringer Ingelheim, Dinesh Khanna Shareholder of: Eicos Sciences, Inc./Civi Biopharma, Inc., Grant/research support from: Dr Khanna was supported by NIH/NIAMS K24AR063120, Consultant of: Acceleron, Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Corbus Pharmaceuticals, Horizon Therapeutic, Galapagos, Roche/Genentech, GlaxoSmithKline, Mitsubishi Tanabe, Sanofi-Aventis/Genzyme, UCB